Improving Language Models in Speech-Based Human-Machine Interaction. (1st February 2013) - Justo, Raquel; Saz, Oscar; Miguel, Antonio; Torres, M. Inés; Lleida, Eduardo
This work focuses on speech-based human-machine interaction. Specifically, a Spoken Dialogue System (SDS) that could be integrated into a robot is considered. Since Automatic Speech Recognition is one of the most sensitive tasks that must be confronted in such systems, the goal of this work is to improve the results obtained by this specific module. In order to do so, a hierarchical Language Model (LM) is considered. Different series of experiments were carried out using the proposed models over different corpora and tasks. The results obtained show that these models provide greater accuracy in the recognition task. Additionally, the influence of the Acoustic Modelling (AM) in the improvement percentage of the Language Models has also been explored. Finally the use of hierarchical Language Models in a language understanding task has been successfully employed, as shown in an additional series of experiments.